2020
DOI: 10.1021/acs.jpcc.0c08413
|View full text |Cite
|
Sign up to set email alerts
|

Highly Asymmetric Optical Properties of β-Ga2O3 as Probed by Linear and Nonlinear Optical Excitation Spectroscopy

Abstract: β-Ga2O3 is a highly promising semiconductor for a deep ultraviolet emitter owing to its wide bandgap, which significantly varies in the range of 4.49 eV to 4.74 eV due to its optical trirefringence in the monoclinic crystal structure (C2h). However, dominant photoluminescence (PL) emissions in β-Ga2O3 occur far below the bandgap, where the underlying PL mechanism has been under intense debate. In order to address this issue, we monitored the most intense PL peaks at 3.0 eV and 3.5 eV at room temperature by emp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
1
18
0
3
Order By: Relevance
“…The large 3PA coefficient (4.75 × 10 –4 cm 3 /MW 2 ) of γ-NaAsSe 2 is most likely due to its low band gap energy ( E g ), as is evident from the strong inverse relation γ ∝ 1/( E g ) 6.5 . Na 0.1 K 0.9 AsS 2 has a much smaller 3PA coefficient (2.31 × 10 –5 cm 3 /MW 2 ) because of its larger band gap, together with electronic band parameters for less probable 3PA, such as dipole matric elements and band curvatures specific to the sulfide Table summarizes the χ eff (2) , LIDT, and γ values of all reported compounds.…”
Section: Resultsmentioning
confidence: 90%
“…The large 3PA coefficient (4.75 × 10 –4 cm 3 /MW 2 ) of γ-NaAsSe 2 is most likely due to its low band gap energy ( E g ), as is evident from the strong inverse relation γ ∝ 1/( E g ) 6.5 . Na 0.1 K 0.9 AsS 2 has a much smaller 3PA coefficient (2.31 × 10 –5 cm 3 /MW 2 ) because of its larger band gap, together with electronic band parameters for less probable 3PA, such as dipole matric elements and band curvatures specific to the sulfide Table summarizes the χ eff (2) , LIDT, and γ values of all reported compounds.…”
Section: Resultsmentioning
confidence: 90%
“…Guo et al found that thermal conductivity along the [010] direction is approximately three times larger than along the [100] direction [13]. Anisotropic nonlinear optical properties in β-Ga 2 O 3 have been reported [14,15]. Liu et al grew β-Ga 2 O 3 epilayers on r-and c-plane sapphire substrates and showed that β-Ga 2 O 3 epilayers on r-plane revealed higher UV responsivity and detectivity [16].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Highly efficient third‐order NLO materials can be used in various applications such as self‐phase modulation, optical switching, four‐wave mixing, and 2PA microscopy/spectroscopy. [ 13 ] In particular, microscopists are interested in the development of a single‐beam nonlinear microscopic approach that combines 2PA, SHG, and/or THG to achieve a better cell image contrast. [ 14 ] However, the commonly used techniques often produce photobleaching and/or cytotoxic effects that significantly reduce cell imaging quality.…”
Section: Introductionmentioning
confidence: 99%